PENGARUH NON PERFORMING FINANCING PEMBIAYAAN MUDHARABAH DAN NON PERFORMING FINANCING PEMBIAYAAN MUSYARAKAH TERHADAP PROFITABILITAS PADA BANK UMUM SYARIAH DI INDONESIA - Sri Mulyaningsih; Iwan Fakhruddin (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2016)
This study aimed to know the influence of non performing financing in Mudharabah system and non performing financing in musyarakah system toward the profitability of the the Islamic banks. A financing channeled to customers potentially leads to financial problems. Financing problematic in the Islamic banks can be seen from the level of non performing financing. The data used in this study was the secondary data in the form of annual financial report in islamic banks during period 2009 up to 2013. The method of data analysis used in this research was multipel linier regression analysis. The samples taken were 33 of data includes 8 Islamic banks during the period of 5 years. The samples taken by using the purposive sampling technique. The results showed that simultan eously non performing financing Mudharabah and non performing financing Musyarakah affected on the profitabilty og Islamic banks, while partially non performing financing mudharabah didn’t affect negatively, but positively affected financing with the significance 0,018 and non performing financing musyarakah didn’t affect the profitability of Islamic banks. Keyword : NPF Mudharabah Financing, NPF Musyarakah Financing, Profitability.